Evaluation of Value Added Tax Collector Appointment Policy in Indonesia from the Perspective of Administrative Simplicity Principle - Army Raynard; Titi Muswati Putranti (Green Publisher Indonesia, 2026)
The Value Added Tax (VAT) serves as a primary instrument of state revenue that requires both effective collection and administrative simplicity. In this context, Indonesia’s policy of appointing specific entities as VAT withholding agents (Wajib Pemungut or WAPU) aims to enhance compliance and fiscal efficiency; however, questions remain as to whether this policy aligns with the principle of ease of administration. This study evaluates the WAPU policy from that perspective using a qualitative, pragmatic approach through an evaluative literature review. The analysis employs the theoretical frameworks of tax administrative efficiency, the ease of administration principle, and public policy evaluation. The findings indicate that the WAPU mechanism effectively improves revenue collection and narrows monitoring gaps but is administratively inefficient due to the shifting of compliance burdens from the tax authority to businesses. The study identifies an imbalance between fiscal efficiency and administrative simplicity, suggesting the need for policy refinement through digital system integration, administrative incentives, and regulatory adjustments to ensure a VAT collection system that is more efficient, equitable, and sustainable.